Somewhat empty meeting grounds: Travelers in South India - Petri Hottola (Annals of Tourism Research, 2014)
Making ‘genuine’ contacts with local people has been defined as one of the ‘pillars’ of the ideology of independent travel. In a groundbreaking time-space budgeting survey among travelers in Kerala, India, a contradictory reality was discovered. Western trav- elers interacted mainly with local service providers, in an instru- mental manner. Spontaneous contacts occurred mostly during their travel days when situations such as sharing a train compart- ment ‘forced’ the interaction. Interestingly, the ‘genuine’ contacts with locals were least common on leisure days when there was maximum freedom to look for them. The interest for difference was apparently satisfied in less demanding engagements. An anal- ysis of the spatiotemporalities of the traveler everyday challenged and gave measure to several assumed features of travel culture.